A nuclear hormone receptor-associated protein that inhibits transactivation by the thyroid hormone and retinoic acid receptors. - Burris, T P (1995)
Nuclear hormone receptors are transcription factors that require multiple protein-protein interactions to regulate the expression of their target genes. Using the yeast two-hybrid system, we identified a protein, thyroid hormone receptor uncoupling protein (TRUP), that specifically interacts with a region of the human thyroid hormone receptor (TR) consisting of the hinge region and the N-terminal portion of the ligand binding domain in a hormone-independent manner. Interestingly, TRUP inhibits transactivation by TR and the retinoic acid receptor but has no effect on the estrogen receptor or the retinoid X receptor in mammalian cells. We also demonstrate that TRUP exerts its action on TR and retinoic acid receptor by interfering with their abilities to interact with their DNA. TRUP represents a type of regulatory protein that modulates the transcriptional activity of a subclass of the nuclear hormone receptor superfamily by preventing interaction with their genomic response elements.